2003
DOI: 10.1038/sj.bjp.0705570
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic group I metabotropic glutamate receptors modulate synaptic transmission in the rat superior colliculus via 4‐AP sensitive K+ channels

Abstract: 1 Group I metabotropic glutamate receptors (mGluRs) are thought to be important modulators of neuronal function in the superior colliculus (SC). Here, we investigated the pharmacology and signalling mechanisms underlying group I mGluR-mediated inhibition of neuronal excitability and synaptic transmission in the rat SC slice. 2 The group I agonist (RS)-3,5-dihydroxyphenylglycine (DHPG) potently depressed synaptically evoked excitatory postsynaptic potentials (EPSPs), currents (EPSCs), and action potentials in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…In the adult mammalian, electrophysiological studies of mGluRs have shown that activation of mGluRs may lead to a range of cellular changes such as the inhibition of calcium and potassium currents, mediation of slow excitatory postsynaptic potential, and the presynaptic inhibition of transmitter release (Anwyl, R, 1999, Losonczy, A et al, 2003, White, AM et al, 2003. In particular, activation of group I mGluRs can contribute to slow-onset potentiation in the hippocampal region of CA1 (Manahan-Vaughan, D, 1997).…”
Section: Active Integration and Transition Of The Mglur Signal Transdmentioning
confidence: 99%
“…In the adult mammalian, electrophysiological studies of mGluRs have shown that activation of mGluRs may lead to a range of cellular changes such as the inhibition of calcium and potassium currents, mediation of slow excitatory postsynaptic potential, and the presynaptic inhibition of transmitter release (Anwyl, R, 1999, Losonczy, A et al, 2003, White, AM et al, 2003. In particular, activation of group I mGluRs can contribute to slow-onset potentiation in the hippocampal region of CA1 (Manahan-Vaughan, D, 1997).…”
Section: Active Integration and Transition Of The Mglur Signal Transdmentioning
confidence: 99%
“…While ionotropic NMDA-, AMPA-, and kainate-type glutamate receptors (iGluRs) mediate fast synaptic transmission, metabotropic glutamate receptors (mGluRs) (mGluR1 and mGluR5) modulate neuronal excitability and development, synaptic plasticity, transmitter release, and memory function via a variety of intracellular second messenger systems [1113]. Functional interactions between ionotropic and group I metabotropic glutamate receptors have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Ohishi et al, 1993;Kinoshita et al, 1998;Cirone et al, 2002b). At the functional level a contribution of group I, II, and III mGluRs to the modulation of synaptic signaling in the superior colliculus of rats Salt 2000, 2001;Cirone et al, 2002a;White et al, 2003) has been reported.…”
Section: Optic Tectummentioning
confidence: 99%